Chromium Environment within Cr-Doped Silico-Aluminophosphate Molecular Sieves from Spin Density Studies - Liao, Yu Kai; Bruzzese, Paolo Cleto; Hartmann, Martin; Poppl, Andreas; Chiesa, Mario (Journal of Physical Chemistry C, 2021)
X-/Q-band electron paramagnetic resonance (EPR) and hyperfine sublevel correlation (HYSCORE) spectroscopies have been employed, in conjunction with density functional theory (DFT) modeling, to determine the location of Cr5+ions in SAPO-5 zeotype materials. The interaction of the unpaired electron of the paramagnetic Cr5+ species with 27Al could be resolved, allowing for the first detailed structural analysis of Cr5+ paramagnetic ions in SAPO materials. The interpretation of the experimental results is corroborated by DFT modeling, which affords a microscopic description of the system investigated. The EPR-active species is found to be consistent with isolated Cr5+ species isomorphously substituted in the framework at P5+ sites.
CRIS-Team Scopus Importer:2021-05-14